2011
DOI: 10.3390/ijms12020865
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bayesian Clustering and Edge Detection Methods for Inferring Boundaries in Landscape Genetics

Abstract: Recently, techniques available for identifying clusters of individuals or boundaries between clusters using genetic data from natural populations have expanded rapidly. Consequently, there is a need to evaluate these different techniques. We used spatially-explicit simulation models to compare three spatial Bayesian clustering programs and two edge detection methods. Spatially-structured populations were simulated where a continuous population was subdivided by barriers. We evaluated the ability of each method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(167 citation statements)
references
References 59 publications
(89 reference statements)
7
158
1
1
Order By: Relevance
“…However, contrary to these authors, the spatially explicit clustering analysis applied in our study also provided evidence for a temporal decrease in genetic admixture, possibly because of the a priori assumption of spatial dependence of individuals that is thought to be biologically sound (Guillot et al, 2005a). Indeed, analyses based on this assumption earlier proved to perform well under weak levels of population differentiation (Guillot, 2008;Safner et al, 2011), in particular for detecting recent barriers to gene flow (Coulon et al, 2006;Safner et al, 2011;Blair et al, 2012). In our study, post-decline population clusters most likely resulted from a progressive connectivity loss at the landscape level, rather than from a distinct geographical barrier to dispersal (Jensen et al, 2013).…”
Section: Discussioncontrasting
confidence: 49%
“…However, contrary to these authors, the spatially explicit clustering analysis applied in our study also provided evidence for a temporal decrease in genetic admixture, possibly because of the a priori assumption of spatial dependence of individuals that is thought to be biologically sound (Guillot et al, 2005a). Indeed, analyses based on this assumption earlier proved to perform well under weak levels of population differentiation (Guillot, 2008;Safner et al, 2011), in particular for detecting recent barriers to gene flow (Coulon et al, 2006;Safner et al, 2011;Blair et al, 2012). In our study, post-decline population clusters most likely resulted from a progressive connectivity loss at the landscape level, rather than from a distinct geographical barrier to dispersal (Jensen et al, 2013).…”
Section: Discussioncontrasting
confidence: 49%
“…Isolation by distance. It has been shown that ADMIXTURE may misidentify ancestral components when the populations tested follow an isolation by distance model (37 Fig. S5).…”
Section: Resultsmentioning
confidence: 99%
“…According to Latch et al (2006), most of the recent advances in clustering techniques have been made in a Bayesian statistical framework to allow simultaneous estimation of many interdependent parameters in complex models. The advantages of utilizing a Bayesian framework in the analysis of genetic experiments have been emphasized and discussed by several authors (Mora et al, 2009;Cané-Retamales et al, 2011;Li et al, 2011;Safner et al, 2011;Arriagada et al, 2012).…”
Section: Introductionmentioning
confidence: 99%